Carbon fiber shell of camera and preparation method of carbon fiber shell
By using a combined design of flexible reinforcement, dynamic crosslinking components, shape memory functional monomer, interface enhancement coating and intelligent functional coating in carbon fiber composite materials, the shortcomings of existing carbon fiber composite materials in impact toughness, interface bonding strength, intelligent response function and long-term stability are solved, and higher comprehensive performance and adaptability to more complex application scenarios are achieved.
Patent Information
- Application Number
- CN202510291504.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing carbon fiber composite materials have shortcomings in impact toughness, interface combination strength, intelligent response function and long-term stability, and cannot meet the rigorous needs of complex application scenarios.
By using a matrix resin design that combines flexible enhancer, dynamic crosslinking components and nanographene, the impact resistance of the carbon fiber shell is enhanced; the shape memory functional monomer is introduced to achieve dynamic recovery of the material; the interface coating constructed by silane coupling agent and nanoparticles is used to improve the interface binding strength; and the intelligent functional coating of the material is realized through the intelligent functional coating of temperature-sensitive polymers and conductive fillers.
It significantly improves the impact toughness and interface bonding strength of the carbon fiber shell, extends the service life of the material, gives the material an intelligent response function, and improves its long-term stability in complex environments.
Smart Images

Figure CN119798928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a carbon fiber shell of a camera and a preparation method thereof. Background Art
[0002] Carbon fiber composite materials are widely used in the field of high-end equipment housings, including camera housings, drone housings, etc., due to their excellent properties such as light weight, high strength, and corrosion resistance. However, as application scenarios become increasingly complex, the performance requirements for materials are not only limited to high strength and light weight, but also include comprehensive improvements in impact toughness, interface bonding strength, long-term stability, and intelligent functions. Therefore, the performance of existing carbon fiber composite materials needs to be optimized to meet more stringent usage requirements.
[0003] In the prior art, the structure of carbon fiber composite materials is mainly composed of carbon fiber reinforcement layer, epoxy resin matrix and simple interface treatment. Although it has certain mechanical properties, it still has the following problems: the matrix material is mainly rigid epoxy resin, which has insufficient impact toughness and is prone to brittle fracture; the interface treatment usually adopts simple physical or chemical methods, resulting in low interface bonding strength, easy to slip or fiber shedding when subjected to force; lack of intelligent response function, unable to dynamically adjust performance or crack monitoring; under long-term aging environment, the matrix and interface performance decline rapidly, limiting its application life in complex environments. Therefore, a new technical solution is urgently needed to solve the above problems through multi-dimensional optimization to improve the comprehensive performance of carbon fiber shells. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a carbon fiber housing for a camera and a preparation method thereof, which solves the problems in the prior art of insufficient impact toughness, low interface bonding strength, lack of intelligent response function and poor long-term stability of the carbon fiber housing.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a carbon fiber housing of a camera and a preparation method thereof, comprising the following components: A carbon fiber reinforcement layer, wherein the carbon fiber is oxidized and coated with an interface coating, wherein the interface coating includes a silane coupling agent and nanoparticles; A matrix resin, wherein the matrix resin is composed of an epoxy resin, a flexibility enhancer, a shape memory functional monomer, a dynamic cross-linking component, a nano-enhanced component and a curing agent; An intelligent functional coating, comprising a temperature-sensitive polymer and a conductive filler.
[0006] Preferably, the carbon fiber reinforced layer uses carbon fiber that has been oxidized with acid solution, the acid solution is composed of nitric acid and sulfuric acid in a volume ratio of 1:3, the oxidation temperature is 60-80° C., and the time is 30-60 minutes.
[0007] Preferably, the interface coating comprises a silane coupling agent and nanoparticles, the silane coupling agent is γ-aminopropyltriethoxysilane, the nanoparticles are nano-silicon dioxide with a particle size of 20 nm, and the mass fraction of the nano-silicon dioxide is 3%-6%.
[0008] Preferably, the epoxy resin in the matrix resin is bisphenol A epoxy resin with a mass fraction of 60%-80%; the flexibility enhancer is polyetheramine with a mass fraction of 10%-20%; and the shape memory functional monomer is tetrafunctional acrylate with a mass fraction of 5%-15%.
[0009] Preferably, the dynamic cross-linking component in the matrix resin is trimethylolpropane borate, with a mass fraction of 3%-8%; the nano-enhanced component includes nano-graphene with a particle size of 5-10nm and nano-cellulose with a particle size of 10-50nm, the mass fraction of the nano-graphene is 2%-5%, and the mass fraction of the nano-cellulose is 1%-3%.
[0010] Preferably, the temperature-sensitive polymer in the smart functional coating is poly(N-isopropylacrylamide) with a mass fraction of 2%-4%; the conductive filler is carbon nanotubes with a diameter of 1-10 nm and a length of 5-15 μm, with a mass fraction of 1%-3%.
[0011] A method for preparing a carbon fiber housing of a camera comprises the following steps: (1) Preparation of matrix resin: epoxy resin and nano-enhanced component are mixed, and after ultrasonic dispersion, flexibility enhancer, shape memory functional monomer and dynamic cross-linking component are added, and after stirring evenly, curing agent is added; (2) Surface treatment of carbon fiber: After the carbon fiber is oxidized in an acid solution, an interface coating is performed using a silane coupling agent and nanoparticles; (3) Laying and molding of composite materials: Laying the treated carbon fiber and matrix resin according to the design direction and molding by vacuum-assisted resin transfer molding; (4) Preparation of intelligent functional coating: coating the surface of the composite material with a coating of thermosensitive polymer and conductive filler.
[0012] Preferably, the frequency of ultrasonic dispersion in step (1) is 30-50 kHz, the time is 30-60 minutes, and the mass ratio of curing agent to epoxy resin is 1:0.3-1:0.4.
[0013] Preferably, the temperature of the acid oxidation in step (2) is 60-80°C and the time is 30-60 minutes; the mass ratio of the silane coupling agent to the solvent in the interface coating treatment is 1:10-1:20, and after coating, the heat treatment is performed at 80-100°C for 1-2 hours.
[0014] Preferably, in step (4), the coating of the temperature-sensitive polymer and the conductive filler is carried out by spraying, and after spraying, the coating is dried at 50-70° C. for 1-2 hours.
[0015] The present invention provides a carbon fiber housing of a camera and a preparation method thereof. The carbon fiber housing has the following beneficial effects: 1. The present invention adopts a matrix resin design that combines a flexibility enhancer, a dynamic cross-linking component and nanographene, so that the shell can dissipate more energy when subjected to a strong impact load and enhance the crack propagation resistance. Compared with the technical solution in the prior art that simply uses a rigid epoxy resin matrix to cause brittle failure of the material, the present invention solves the technical bottleneck of poor material impact resistance.
[0016] 2. The present invention introduces shape memory functional monomers to give the shell the ability to return to its original shape after deformation, thereby extending the service life of the material. The existing technology mostly relies on rigid materials for protection and cannot maintain the integrity of the shape after impact. The present invention effectively solves the problem of irreversible damage to traditional shells after impact deformation and has unpredictable advantages.
[0017] 3. The present invention adopts an interface coating system constructed by a silane coupling agent and nanoparticles, which significantly improves the interface bonding strength between carbon fiber and matrix resin, thereby optimizing the load transfer efficiency. Compared with the prior art solution of treating carbon fiber only by surface oxidation, the present invention not only enhances chemical bonding, but also uses nanoparticles to achieve physical intercalation, solving the problem of insufficient interface bonding strength.
[0018] 4. The present invention coats the shell surface with temperature-sensitive polymer and conductive network coating, so that the material has intelligent functions, can dynamically adjust the rigidity according to the ambient temperature, and monitor the health status of the shell in real time through resistance changes. Compared with the design of the prior art that only considers structural functions, the present invention solves the problem that the traditional shell has a single performance and cannot be monitored in complex environments, and innovatively realizes the combination of self-adaptation and real-time feedback. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the method flow of the present invention; Figure 2 It is a broken line schematic diagram of Experimental Example 1 of the present invention; Figure 3 It is a broken line schematic diagram of Experimental Example 2 of the present invention; Figure 4 It is a broken line schematic diagram of Experimental Example 3 of the present invention; Figure 5 It is a broken line schematic diagram of Experimental Example 4 of the present invention; Figure 6 It is a broken line diagram of Experimental Example 5 of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 -Attached Figure 6 The embodiment of the present invention provides a carbon fiber housing of a camera and a method for preparing the same, comprising the following steps: 1. Composition design 1.1 Matrix resin formula design The matrix resin adopts a bifunctional epoxy resin system, which includes a shape memory matrix and a dynamic cross-linking component. By introducing a flexible enhancer and a nano-enhanced component, the toughness and crack propagation resistance of the material under high impact loads are improved, while providing the shape memory function of the material. Its components and design basis are as follows: Epoxy resin (60–80wt%): Bisphenol A epoxy resin has excellent mechanical properties and chemical stability, and is the first choice for high-performance matrix resins. The epoxy group and the curing agent form a highly cross-linked network structure to ensure the strength and rigidity of the matrix material.
[0022] Flexibility enhancer (10–20wt%, such as polyetheramine D-230): The long chain structure of polyetheramine provides flexible molecular segments, effectively alleviating the brittleness of the cross-linked network. At the same time, its terminal amine groups react with epoxy groups to participate in cross-linking and enhance the overall toughness of the material.
[0023] Shape memory functional monomers (5–15wt%, such as tetrafunctional acrylates): By adding shape memory monomers, the material is given shape memory function, which allows it to return to its original shape after the external force is removed. This function is particularly important in the impact deformation of camera housings to avoid permanent deformation of the material.
[0024] Dynamic crosslinking component (3–8 wt %, such as trimethylolpropane borate): The dynamic cross-linking component provides reversible chemical bonds (such as boron-oxygen bonds). When cracks are formed, they effectively dissipate energy through the breaking and reconstruction of dynamic bonds, thereby delaying crack propagation.
[0025] Nano-enhanced components: Nanographene (2–5wt%, particle size 5–10nm): provides mechanical reinforcement and thermal conductivity of the matrix, and improves the distribution of matrix stress at the crack tip.
[0026] Nanocellulose (1–3wt%, particle size 10–50nm): As rigid nanoparticles, it forms a physical bond with epoxy resin molecules and improves the elastic modulus of the matrix.
[0027] Curing agent (triethylenetetramine, epoxy resin mass ratio 1:0.3–1:0.4): provides a cross-linking reaction for the matrix, so that the matrix forms a three-dimensional cross-linked network structure.
[0028] 1.2 Carbon fiber interface coating design Carbon fibers are treated with an interfacial coating to enhance the fiber-matrix interfacial bonding strength. The interfacial coating includes a silane coupling agent and nanoparticles, which provide chemical bonding and physical reinforcement, respectively.
[0029] Silane coupling agent (1–2wt%, such as KH550): Silane coupling agent forms silicon-oxygen bonds (Si–O–Si) on the surface of carbon fiber and reacts with the epoxy group through the amino group to achieve a chemical bonding layer on the fiber surface.
[0030] Nanoparticles (3–6wt%, 20nm nano-silica): form a reinforcing layer with a physical interlocking effect on the fiber surface, further improving the interface strength.
[0031] 1.3 Intelligent functional coating design Smart functional coatings include temperature-sensitive polymers and conductive fillers for dynamic response and real-time health monitoring of camera housings.
[0032] Thermosensitive polymers (2–4wt%, such as poly (N-isopropylacrylamide) PNIPAM): The coating is sensitive to temperature changes and is flexible at 40–50°C and returns to a rigid state below this temperature.
[0033] Conductive fillers (1–3wt%, such as carbon nanotubes): form a conductive network in the coating for electrical signal feedback of crack growth or impact damage.
[0034] 2. Preparation process and mechanism analysis Step 1: Preparation of base resin The epoxy resin was mixed with nanographene and nanocellulose and dispersed by ultrasound (frequency 30–50 kHz, time 30–60 min) to ensure that the nanoparticles were evenly dispersed.
[0035] The flexible reinforcing agent (10–20 wt%) and the dynamic cross-linking component (3–8 wt%) were added and stirred at 70–90 °C for 1–2 hours to form a flexible reinforced matrix.
[0036] Add the shape memory functional monomer (5–15 wt%) and stir for 30–60 minutes to ensure uniform dissolution.
[0037] Add curing agent (1:0.3–0.4 by weight ratio of epoxy resin) and degas in a vacuum environment (<200Pa, time 15–30 minutes).
[0038] Step 2: Surface treatment of carbon fiber The carbon fibers were treated with a nitric acid / sulfuric acid mixture (1:3) at 60–80°C for 30–60 minutes to remove surface impurities and increase active functional groups.
[0039] The silane coupling agent (1–2 wt%) was dissolved in ethanol (1:10–1:20) and the carbon fiber was impregnated for 30–60 min and then dried and heat treated at 80–100 °C for 1–2 h.
[0040] Coating with nanoparticles (3–6wt%) to form a physical reinforcement layer.
[0041] Step 3: Lay-up of composite materials The carbon fibers and matrix resin are laid alternately according to the design direction.
[0042] The molded products were molded using the vacuum assisted resin transfer molding (VARTM) process, pre-cured at 80–100°C for 3–4 hours, and then heated to 120–150°C to complete the curing.
[0043] Example 1: A method for preparing a high-toughness carbon fiber shell Preparation of base resin Weigh 80g of bisphenol A epoxy resin (E-51) and place it in a stirring device, add 2g of nanographene (particle size 5-10nm) and 1g of nanocellulose (particle size 20nm), and ultrasonically disperse it. The frequency is set to 40kHz and the time is controlled at 40 minutes. Then add 16g of polyetheramine (D-230) and stir at 80℃ for 1 hour to fully dissolve and react. Then, add 5g of trimethylolpropane borate and continue stirring for 30 minutes. Finally, add 10g of tetrafunctional acrylate, stir evenly, and add curing agent triethylenetetramine, according to the epoxy resin mass ratio of 1:0.3. Degas in a vacuum environment for 20 minutes and set aside.
[0044] Interface treatment of carbon fiber Take T700 carbon fiber and treat it with a mixed acid solution of nitric acid and sulfuric acid (volume ratio 1:3), the temperature is controlled at 70°C, and the treatment time is 40 minutes. Rinse with deionized water until neutral, and dry in a 60°C oven for 2 hours. Dissolve the silane coupling agent KH550 in ethanol (mass ratio 1:15), immerse the treated carbon fiber in the solution, and let it stand for 50 minutes. After taking it out, heat treat it at 90°C for 1.5 hours. Then, disperse 3g of nano-silica and a small amount of water into a slurry, spray it evenly on the surface of the carbon fiber, and dry it at 80°C for 1 hour.
[0045] Composite material molding The interface-modified carbon fibers were laid in a 0° / 90° staggered direction and alternately impregnated with the prepared matrix resin. The vacuum-assisted resin transfer molding (VARTM) process was used for molding, and the vacuum pressure was set to 200 Pa. The carbon fibers were cured at 80°C for 4 hours, then heated to 150°C for 2 hours. Finally, post-treatment was performed at 180°C for 1 hour.
[0046] Intelligent coating preparation A 2 wt% poly (N-isopropylacrylamide) (PNIPAM) aqueous solution was sprayed on the surface of the composite material, evenly coated, and dried at 50 ° C for 1 hour. Then a carbon nanotube solution (1.5 wt%, dispersed in dimethyl sulfoxide) was coated, ultrasonicated for 40 minutes, and then dried at 60 ° C for 1 hour.
[0047] Effect: By optimizing the matrix resin and interface reinforcement, the impact toughness of the shell is significantly improved. The shape memory matrix can restore its original shape after impact, and the coating provides temperature-sensitive response and health monitoring functions, solving the shortcomings of traditional shells that are fragile and unmonitorable.
[0048] Example 2: A carbon fiber shell suitable for extreme environments Preparation of base resin Take 70g of epoxy resin (E-51), add 3g of nanographene (particle size 8nm) and 2g of nanocellulose (particle size 30nm), and ultrasonically disperse for 50 minutes at a frequency of 45kHz. Add 12g of polyetheramine, stir for 30 minutes, and then add 6g of disulfide bond crosslinker. Heat to 85℃, continue stirring for 40 minutes, and finally add 15g of shape memory monomer (tetrafunctional acrylate). The degassing time is 15 minutes.
[0049] Carbon fiber surface treatment The carbon fiber was placed in a mixed acid solution (nitric acid / sulfuric acid, 1:4 volume ratio) at 65°C for 50 minutes. After cleaning, it was dried. Silane coupling agent (1.5wt%) was dissolved in isopropanol and impregnated into the carbon fiber for 40 minutes. It was then heat treated at 90°C for 2 hours. The carbon fiber was sprayed with 5wt% nano-silica solution and dried for 70 minutes.
[0050] Composite material molding The carbon fiber is laid in a ±45° direction and coated with matrix resin at intervals. The hand lay-up method is used for preliminary shaping, and the initial curing is carried out at 100°C for 3 hours and then at 180°C for 2 hours.
[0051] Coating introduction 1% nanographene is added to the thermosensitive polymer solution to improve weather resistance. After spraying, it is cured at 70°C. The conductive coating is formed by spraying the carbon nanotube solution, the temperature is set at 65°C, and the drying is completed.
[0052] Effect: Under high temperature or complex environment, the rigidity and flexibility of the shell can be adjusted dynamically. The interface strength is significantly improved, the crack propagation is suppressed, and the coating increases the real-time monitoring capability.
[0053] Embodiment 3: A carbon fiber shell combining lightness and intelligence Preparation of base resin Add epoxy resin (75g) to a mechanical stirring device, add 2.5g nanocellulose, stir for 30 minutes, then add 10g polyetheramine. Heat to 70°C, add 7g dynamic crosslinker (borate). After stirring for 1 hour, add 10g shape memory monomer, stir evenly and set aside.
[0054] Carbon fiber processing The carbon fiber was treated with 70°C nitric acid for 40 minutes, washed and dried, coated with a silane coupling agent solution with a coating concentration of 1wt% and immersed for 50 minutes, then heat treated at 80°C for 1 hour and dried.
[0055] Laying and curing The layers were laid in the 0° / 90° direction, and the resin was introduced into the gaps between the fibers using a vacuum-assisted process (negative pressure 200Pa). The curing temperature was 90°C for 2 hours, and then the temperature was raised to 140°C for 1.5 hours.
[0056] Coating preparation The carbon nanotube solution was coated on the shell surface and evenly covered by roller coating, and the drying temperature was 60° C. Then the PNIPAM aqueous solution was sprayed and dried.
[0057] Effect: The lightweight design achieves excellent mechanical properties, the coating gives the shell intelligent characteristics, and the health monitoring function performs outstandingly, solving the problem of single function of traditional shells.
[0058] Comparative Example 1: Comparison of base resin without dynamic crosslinking component Comparative Example 1, the formula of the base resin is adjusted as follows: Preparation of base resin Add 2g of nanographene and 1g of nanocellulose to 80g of epoxy resin (E-51), and disperse by ultrasound (40kHz, 40 minutes). Add 16g of polyetheramine (D-230), heat to 80°C and stir for 1 hour. Then add 10g of tetrafunctional acrylate, stir evenly, add curing agent triethylenetetramine, mix according to the epoxy resin mass ratio of 1:0.3, degas for 20 minutes, and set aside.
[0059] No trimethylolpropane borate or other dynamic crosslinking components are added.
[0060] The remaining steps The carbon fiber processing, interface coating design, composite material laying and molding steps are the same as those in Example 1 and are not adjusted.
[0061] Comparative Example 2: Comparison of interfacial coating without introduction of nanoparticles Comparative Example 1, the interface coating of the carbon fiber is changed to a chemical bonding layer using only a silane coupling agent, and no physical reinforcement layer is added: Carbon fiber processing Take T700 carbon fiber, treat it with mixed acid (nitric acid and sulfuric acid, volume ratio 1:3) at 70℃ for 40 minutes, wash and dry it. Silane coupling agent KH550 is dissolved in ethanol solution (1:15 mass ratio), and the carbon fiber is impregnated for 50 minutes, and then heat treated at 90℃ for 1.5 hours.
[0062] Uncoated nanosilica particles.
[0063] The remaining steps The preparation of matrix resin, composite material laying and smart coating spraying are all carried out according to the process of Example 1.
[0064] Comparative Example 3: Comparison without the introduction of shape memory functional monomer Comparative Example 2, the composition of the base resin is adjusted as follows: Preparation of base resin Weigh 70g of epoxy resin (E-51), add 3g of nanographene and 2g of nanocellulose, and disperse by ultrasound (45kHz, 50 minutes). Add 12g of polyetheramine, stir at 80°C for 40 minutes, then add 6g of trimethylolpropane borate, and continue stirring for 1 hour.
[0065] No tetrafunctional acrylates or other shape memory monomers are added.
[0066] Vacuum degassing for 15 minutes and set aside.
[0067] The remaining steps The carbon fiber surface treatment, layer formation and coating preparation are consistent with those in Example 2 without any adjustment.
[0068] Comparative Example 4: Comparison of carbon fiber surface without interface treatment Comparative Example 3, the processing steps of adjusting the carbon fiber are as follows: Carbon fiber processing The T700 carbon fiber without surface treatment is directly used without mixed acid oxidation treatment and silane coupling agent impregnation.
[0069] The remaining steps of base resin preparation, lamination and smart coating remain the same as in Example 3.
[0070] Comparative Example 5: Comparison without the introduction of smart functional coating Comparative Example 3, the process step of spraying the smart coating is eliminated: Preparation of matrix resin, carbon fiber processing, composite material molding All the steps were carried out according to the process of Example 3 without any adjustment.
[0071] Coating preparation The PNIPAM temperature-sensitive coating and the carbon nanotube conductive coating were not sprayed, and the final shell did not have an intelligent functional coating.
[0072] Comparative Example 6: The nano-enhanced component in the matrix resin is replaced by a conventional inorganic filler Comparative Example 1, the nano-enhanced component in the matrix resin is adjusted as follows: Preparation of base resin 4 g of ordinary micron-sized silicon powder (particle size 5 μm) was added to 80 g of epoxy resin (E-51) to replace nanographene and nanocellulose. The remaining formulation components and process conditions (including the addition of flexibility enhancer and dynamic cross-linking component and the stirring temperature and time) were kept the same.
[0073] The remaining steps Carbon fiber processing, interface coating design, layer formation and intelligent coating preparation are all carried out according to the process of Example 1.
[0074] Comparative Example 7: Dynamic cross-linking component replaced by conventional cross-linking component In Comparative Example 1, the dynamic crosslinking component (trimethylolpropane borate) is replaced by a conventional crosslinking agent.
[0075] Preparation of base resin Add 2g of nanographene and 1g of nanocellulose to 80g of epoxy resin, and disperse them by ultrasonication for 40 minutes at a frequency of 40kHz. Add 16g of polyetheramine and 7g of hydroquinone (conventional crosslinking agent), and stir at 80°C for 1 hour. The remaining components and steps remain unchanged.
[0076] The remaining steps The interface treatment of carbon fiber, composite material layup molding and coating process are consistent with Example 1.
[0077] Experiment 1: Impact resistance test Experimental procedures Sample preparation Samples of Example 1, Comparative Example 1 and Comparative Example 6 were prepared, and each sample was cut into a test piece of 50 mm×50 mm×3 mm, and the surface was polished to eliminate surface defects. The thickness of each group of samples was ensured to be uniform to avoid distortion of the test results due to thickness deviation.
[0078] Experimental setup Using a drop hammer impact tester, the impact energy of the drop hammer was adjusted to 20J, 40J and 60J to simulate impact loads of different intensities. The mass of the drop hammer was 5kg, and the impact heights were calculated to be 0.4m, 0.8m and 1.2m respectively. Each group of samples was tested 3 times at each impact energy, and the maximum crack length, damage area and damage morphology of the samples were recorded.
[0079] Testing Process Fix the sample horizontally on the base of the impact machine to ensure that the force-bearing surface is in flat contact with the drop weight.
[0080] Adjust the impact height of the drop hammer one by one, apply impact loads of different energies, and observe and record the crack morphology and expansion of the sample surface after impact.
[0081] Measure the crack length (accurate to 0.1 mm), take photos of the damaged area, and calculate the damaged area using image processing software.
[0082] Data Recording The maximum crack length, damage area and failure mode of each group of samples under different impact energies were recorded.
[0083] Experimental data table Table Name:
[0084] The dynamic crosslinking design of the matrix resin plays a crucial role. In Example 1, the dynamic crosslinking component effectively dissipates stress at the crack tip by breaking and reconstructing reversible chemical bonds. This molecular-level dissipation mechanism inhibits the rapid expansion of cracks. In contrast, Comparative Example 1 does not have a dynamic crosslinking component, the matrix toughness is insufficient, and cracks are prone to rapid expansion along the weak points of the crosslinking network, resulting in a significant increase in the damaged area and crack length.
[0085] At the same time, the introduction of nano-reinforced components further optimizes the matrix performance. Nanographene forms a uniformly distributed reinforcement phase in Example 1, effectively dispersing the local stress at the crack tip. This dispersion effect is particularly evident in the early stages of crack formation, which can significantly slow down the propagation speed of the crack. In Comparative Example 6, the micron silicon powder has a limited reinforcement effect due to its large particle size, and it is easy to agglomerate in the matrix, which introduces stress concentration points and accelerates the expansion of the crack.
[0086] In addition, the flexibility enhancer of the matrix resin works synergistically with the dynamic cross-linking component, further demonstrating the impact resistance advantage of Example 1. The presence of the flexible molecular segment enables the matrix to exhibit a stronger energy absorption capacity under high load, thereby reducing the damaged area. However, due to the lack of this synergistic mechanism, Comparative Examples 1 and 6 exhibit a higher tendency to brittle failure. The crack morphology in Example 1 is more uniform, and the damaged area is concentrated and limited, which fully verifies the design rationality of the present invention.
[0087] Experiment 2: Interface bonding strength test Experimental procedures Sample preparation Samples of Example 1, Comparative Example 2 (no nanoparticle interface reinforcement layer was introduced) and Comparative Example 4 (no interface treatment was performed on the carbon fibers) were prepared, and the sample size was 25 mm×25 mm×2 mm.
[0088] The laying direction of the carbon fiber is 0°, and the matrix resin is fully impregnated with the carbon fiber layer before forming to ensure that there are no obvious defects inside the sample. The surface of the sample is simply polished to ensure that the surface is flat.
[0089] Experimental setup A short beam shear test fixture was used, the loading equipment was an electronic universal testing machine, the loading rate was set to 1 mm / min, and the maximum load range was 0–500 N.
[0090] The four-point loading mode is adopted to ensure that the sample is evenly stressed during the loading process.
[0091] Testing Process Fix the sample in the shear test fixture and adjust the contact point between the loading head and the sample to ensure that there is no initial slip during the loading process.
[0092] Start the equipment and gradually increase the shear force according to the loading rate. Record the maximum shear force value of the sample and the failure mode (such as fiber shedding, interface slippage, matrix cracking, etc.) at failure.
[0093] Each group of samples was tested 3 times, the average value was taken and the error range was analyzed.
[0094] Calculation method According to the maximum shear force Calculate the shear strength using the shear stress area :
[0095]
[0096] Among them, the shear force area is the loading length of the sample multiplied by the sample thickness.
[0097] Data Recording The maximum shear strength (MPa) and failure mode of each group of samples were recorded and compared and analyzed.
[0098] Experimental data table Table Name:
[0099] The nanoparticle design of the interface enhanced coating is the key to this performance improvement. In Example 1, the nano-silica particles significantly improved the fiber-matrix interface bonding strength through surface intercalation. The nanoparticles can fill the microscopic depressions on the fiber surface, so that the matrix obtains a higher contact area in the interface area, thereby improving the shear load transfer efficiency. In Comparative Example 2, nanoparticles were not introduced, and interface slip became its main failure mode, indicating that the chemical bonding of the silane coupling agent alone cannot fully suppress the slip behavior.
[0100] Oxidation and interface treatment of the carbon fiber surface also play an important role in bonding strength. In Example 1, after the carbon fiber was treated with acid, a large number of polar functional groups were formed on the surface. The reaction of these functional groups with the silane coupling agent generated a strong bonding interface, which further improved the interfacial bonding strength. On the contrary, in Comparative Example 4, no surface treatment was performed, the carbon fiber surface lacked active points, and the matrix and the fiber were mainly weakly physically bonded, resulting in fiber shedding as the main failure form.
[0101] In addition, the interface coating design of Example 1 achieves the dual effects of chemical bonding and physical enhancement through the synergistic effect of silane coupling agent and nanoparticles. Under the action of shear force, this multilayer interface design effectively delays the occurrence of slip failure. However, due to the lack of this synergistic mechanism, Comparative Examples 2 and 4 show lower shear strength. It can be seen that Example 1 significantly improves the interface load transfer efficiency and the overall performance of the material by comprehensively optimizing the interface structure.
[0102] Experiment 3: Dynamic recovery performance test Experimental procedures Sample preparation Samples of Example 2, Comparative Example 1 (no dynamic cross-linking component added) and Comparative Example 3 (no shape memory functional monomer introduced) were prepared, and the sample size was 50 mm×50 mm×2 mm, ensuring that the sample surface was flat and the thickness was uniform.
[0103] Experimental setup A three-point bending test was conducted using an electronic universal testing machine with a loading rate of 2 mm / min. The bending force was controlled at 15 MPa and the deformation curvature after loading was recorded. After loading, the sample was transferred to a thermostat with the temperature set at 60°C to observe the deformation recovery process.
[0104] Testing Process Place the sample in a three-point bending test fixture, with the support point spacing fixed at 40 mm. Apply a gradually increasing force to the center of the sample until the bending stress reaches 15 MPa. Record the maximum bending deformation of the sample. .
[0105] After stopping loading, transfer the sample to a 60°C constant temperature box and observe the deformation recovery. Measure the residual deformation every 1 minute. .
[0106] Record the final deformation recovery rate (%) and recovery time (minutes) of the sample.
[0107]
[0108] Data Recording Each group of samples was tested three times, and the maximum deformation, residual deformation, recovery rate and recovery time were recorded.
[0109] Experimental data table Table Name:
[0110] The role of the dynamic cross-linking component is particularly prominent in Example 2. Trimethylolpropane borate forms reversible boron-oxygen bonds. After the sample is subjected to bending force, the breaking of its bonds can effectively dissipate energy and prevent the occurrence of permanent plastic deformation. Under recovery conditions, these dynamic bonds can rebuild the molecular cross-linking network and quickly promote the recovery of deformation. This mechanism is completely missing in Comparative Example 1, so effective dynamic recovery cannot be achieved, but a large residual deformation is presented.
[0111] Shape memory functional monomers further demonstrate their value in terms of material recovery rate and recovery time. In Example 2, the introduction of tetrafunctional acrylates gives the matrix heat-induced shape memory properties, which originate from the dynamic physical cross-linking network of the shape memory polymer. When the sample is in an environment of 60°C, the physical cross-linking points relax, and the molecular segments of the material can restore their initial arrangement state, thereby accelerating shape recovery. In Comparative Example 3, no shape memory monomers were introduced, and only dynamic chemical cross-linking was relied upon, so the recovery process was limited, the residual deformation was large, and the recovery time was significantly prolonged.
[0112] In addition, the synergistic effect of the dynamic cross-linking component and the shape memory monomer greatly improves the overall dynamic response performance of the material. The combination of the two in Example 2 enables the material to have both high energy dissipation capacity and rapid recovery after the external force is released. This synergy is missing in both Comparative Examples 1 and 3, which is manifested as high residual deformation or significantly prolonged recovery time. The rapid recovery characteristics of Example 2 verify the rationality and advantages of the matrix resin design, and also prove the significant innovation of the present invention in terms of dynamic recovery performance.
[0113] Experiment 4: Smart coating response and monitoring capability test Experimental procedures Sample preparation Samples of Example 3, Comparative Example 5 (without introduction of smart functional coating) and Comparative Example 7 (dynamic cross-linking component replaced with conventional cross-linking agent) were prepared, with a sample size of 50 mm×50 mm×3 mm and a smooth surface treatment to ensure uniform coverage of the coating.
[0114] Thermosensitive response experiment Place the sample on an adjustable hot plate, gradually increase the temperature from 25°C to 60°C, with a temperature increase gradient of 10°C, maintain the constant temperature for 10 minutes, and record the hardness change of the coating surface.
[0115] The modulus of the coating surface was measured using a nanoindenter, and the numerical changes at different temperatures were recorded. Each sample was tested 3 times and the average value was taken.
[0116] Crack monitoring experiment A tensile test was used to simulate crack propagation. The test equipment was an electronic universal testing machine and the loading rate was set to 1 mm / min.
[0117] The resistance change of the smart conductive coating is measured in real time during the stretching process, and the generation and expansion of the crack are inferred from the change trend of the resistance value. Each sample is tested three times to ensure data stability.
[0118] The crack length was measured by microscopic observation after stretching and correlated with the resistance change.
[0119] Data Recording The temperature-modulus curve, crack length, resistance variation range and sensitivity of the conductive network (the slope of the resistance variation rate with crack length) of the coating were recorded respectively.
[0120] Experimental data table Table Name:
[0121] The dynamic response characteristics of the thermosensitive coating are particularly prominent in Example 3. In the temperature range of 25°C to 60°C, the modulus of the coating surface shows a clear downward trend. This behavior originates from the phase transition characteristics of the PNIPAM thermosensitive polymer. When the temperature rises to above 40°C, the molecular segments of the coating relax, which reduces the modulus and enhances the flexibility. This characteristic provides an advantage for the performance adaptability of the housing in high temperature environments. However, in Comparative Example 5, no thermosensitive polymer was introduced, and the modulus remained basically constant, indicating that its coating lacks dynamic response capability and cannot adjust rigidity according to temperature.
[0122] The crack monitoring capability of the conductive coating is another key feature of Example 3. During the stretching process, the carbon nanotube network structure in the coating is destroyed due to crack expansion, resulting in a significant increase in resistance. This resistance change is not only highly sensitive to the crack length (ΔR / ΔL is significantly higher than that of Comparative Example 7), but also can reflect the development status of the crack in real time. However, since Comparative Example 5 is not coated with a conductive network, it is completely unable to provide a monitoring function during the crack generation process; although Comparative Example 7 introduces a conductive coating, due to the lack of a dynamic cross-linking component in the matrix, the crack expands too quickly and the conductive network cannot remain stable, resulting in a low sensitivity.
[0123] The excellent performance of the coating in Example 3 is due to the synergistic effect of the two coating components. The temperature-sensitive polymer not only gives the coating dynamic response characteristics, but also improves the adaptability of the conductive network during the stretching process, so that the coating can maintain a higher sensitivity in the early stage of crack propagation. In the comparative example, the coating lacks this synergy and exhibits a lower monitoring ability or is completely unable to monitor cracks. Through the combination of temperature sensitivity and conductive functions, Example 3 demonstrates excellent versatility in complex environments, and this design innovation is irreplaceable.
[0124] Experiment 5: Long-term aging performance test Experimental procedures Sample preparation Samples of Example 1, Example 3, Comparative Example 2 (without the introduction of the nanoparticle interface enhancement layer) and Comparative Example 5 (without the introduction of the smart functional coating) were prepared, and the size of each sample was 100 mm×100 mm×3 mm. The surface of the sample remained flat without obvious defects.
[0125] Experimental setup The samples were exposed to alternating environments of high temperature, high humidity and ultraviolet aging to simulate long-term service conditions. The specific environmental parameters are as follows: High temperature and high humidity environment: 85°C, relative humidity 85%, for 24 hours; UV aging environment: UV wavelength 320–400nm, illumination 10W / m², lasting 24 hours.
[0126] The samples were alternately cycled in two environments for a test period of 30 days, and samples were taken every 5 days to test the mechanical properties (tensile strength and shear strength).
[0127] Testing Process Aging treatment Place the sample in a high temperature and high humidity environment box for 24 hours, then move it to a UV aging box and expose it for another 24 hours to complete a cycle. Continue for 30 days.
[0128] Mechanical properties test The samples were taken out from the aging environment every 5 days and tested after cooling to room temperature. The tensile strength and shear strength of the samples were tested using an electronic universal testing machine.
[0129] Tensile test: The sample stretching speed is 2mm / min, the maximum tensile load is recorded, and the tensile strength is calculated.
[0130] Shear test: Use the short beam shear method with a loading rate of 1 mm / min, record the maximum shear load, and calculate the shear strength.
[0131] Data Recording The tensile strength and shear strength of each sample at each sampling time were recorded, and the performance decline rate was calculated.
[0132] Experimental data table Table Name:
[0133] The interface enhancement of nanoparticles plays a key role in improving long-term aging performance. In Examples 1 and 3, the interface coating significantly improves the interfacial bonding strength between the fiber and the matrix through the synergistic effect of the silane coupling agent and nano-silicon dioxide. Under aging conditions, the bonding performance at the interface remains stable, and the crack propagation of the matrix is effectively suppressed. This effect is obviously missing in Comparative Example 2, where the interface without nanoparticle coating rapidly degrades under ultraviolet and high humidity conditions, and the shear strength decreases significantly.
[0134] The introduction of smart coatings also plays a role in delaying aging damage. In Example 3, the coating coated with PNIPAM thermosensitive polymer and carbon nanotube network can dynamically respond to changes in temperature and humidity in the aging environment, reduce the stress concentration of the substrate, and slow down the formation of microcracks. Comparative Example 5 lacks this smart coating protection, and microcracks on the surface of the material develop faster in the ultraviolet aging environment, resulting in a rapid decrease in tensile and shear strength.
[0135] In addition, the dynamic cross-linking component provides additional support for the long-term stability of the material. The dynamic cross-linking network of Example 1 and Example 3 repairs the minor damage inside the matrix during the aging process through chemical bond reconstruction, so that the overall performance decline of the material is significantly lower than that of the comparative sample. The materials lacking a dynamic cross-linking mechanism in Comparative Examples 2 and 5 show a significant failure trend after long-term aging. Overall, the long-term stability advantage of Example 1 and Example 3 stems from multi-level collaborative optimization, from the matrix to the interface to the coating, forming a comprehensive protection system, which significantly improves the durability of the material.
[0136] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A carbon fiber housing for a camera, characterized in that: It includes the following components: A carbon fiber reinforcement layer, wherein the carbon fiber is oxidized and coated with an interface coating, wherein the interface coating includes a silane coupling agent and nanoparticles; A matrix resin, wherein the matrix resin is composed of an epoxy resin, a flexibility enhancer, a shape memory functional monomer, a dynamic cross-linking component, a nano-enhanced component and a curing agent; An intelligent functional coating, comprising a temperature-sensitive polymer and a conductive filler.
2. The carbon fiber housing of a camera according to claim 1, characterized in that: The carbon fiber reinforcement layer uses carbon fiber that has been oxidized by acid solution, wherein the acid solution is composed of nitric acid and sulfuric acid in a volume ratio of 1:3, the oxidation temperature is 60-80° C., and the oxidation time is 30-60 minutes.
3. The carbon fiber housing of a camera according to claim 1, characterized in that: The interface coating comprises a silane coupling agent and nanoparticles, wherein the silane coupling agent is γ-aminopropyltriethoxysilane, and the nanoparticles are nano-silicon dioxide with a particle size of 20 nm, and the mass fraction of the nano-silicon dioxide is 3%-6%.
4. The carbon fiber housing of a camera according to claim 1, characterized in that: The epoxy resin in the base resin is bisphenol A epoxy resin with a mass fraction of 60%-80%; the flexibility enhancer is polyetheramine with a mass fraction of 10%-20%; and the shape memory functional monomer is tetrafunctional acrylate with a mass fraction of 5%-15%.
5. The carbon fiber housing of a camera according to claim 1, characterized in that: The dynamic cross-linking component in the matrix resin is trimethylolpropane borate, with a mass fraction of 3%-8%; the nano-enhanced component includes nano-graphene with a particle size of 5-10nm and nano-cellulose with a particle size of 10-50nm, the mass fraction of the nano-graphene is 2%-5%, and the mass fraction of the nano-cellulose is 1%-3%.
6. The carbon fiber housing of a camera according to claim 5, characterized in that: The temperature-sensitive polymer in the intelligent functional coating is poly (N-isopropylacrylamide) with a mass fraction of 2%-4%; the conductive filler is carbon nanotubes with a diameter of 1-10nm and a length of 5-15μm with a mass fraction of 1%-3%.
7. A method for preparing a carbon fiber housing of a camera, according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparation of matrix resin: epoxy resin and nano-enhanced component are mixed, and after ultrasonic dispersion, flexibility enhancer, shape memory functional monomer and dynamic cross-linking component are added, and after stirring evenly, curing agent is added; (2) Surface treatment of carbon fiber: After the carbon fiber is oxidized in an acid solution, an interface coating is performed using a silane coupling agent and nanoparticles; (3) Laying and molding of composite materials: Laying the treated carbon fiber and matrix resin in the designed direction and molding by vacuum-assisted resin transfer molding; (4) Preparation of intelligent functional coating: coating the surface of the composite material with a coating of thermosensitive polymer and conductive filler.
8. The method for preparing a carbon fiber housing of a camera according to claim 7, characterized in that: The frequency of the ultrasonic dispersion in step (1) is 30-50 kHz, the time is 30-60 minutes, and the mass ratio of the curing agent to the epoxy resin is 1:0.3-1:0.
4.
9. The method for preparing a carbon fiber housing of a camera according to claim 7, characterized in that: The temperature of the acid solution oxidation in step (2) is 60-80°C and the time is 30-60 minutes; the mass ratio of the silane coupling agent to the solvent in the interface coating treatment is 1:10-1:20, and after coating, the heat treatment is performed at 80-100°C for 1-2 hours.
10. The method for preparing a carbon fiber housing of a camera according to claim 7, characterized in that: In the step (4), the coating of the temperature-sensitive polymer and the conductive filler is carried out by spraying, and after spraying, the coating is dried at 50-70° C. for 1-2 hours.
Citation Information
Patent Citations
Micro / nano-graphite sheet epoxy resin matrix / modified carbon fiber composite material and preparation method thereof
CN109504036A
Self-repairing carbon nanotube modified epoxy resin material and preparation method thereof
CN111471277A
Secondary battery and device including the same
CN114424381A
Method for improving interfacial strength of carbon fiber / epoxy resin composite material
CN116874834A
Shape memory material with electrical response characteristics and its prepn process
CN1637067A
Cited By
Composite material hollow plate and preparation method thereof
CN121424766A
High-toughness epoxy resin-based carbon fiber prepreg and preparation method thereof
CN122011687A